Arabinogalactan Protein-Like Proteins From Ulva lactuca Activate Immune Responses and Plant Resistance in an Oilseed Crop - Přerovská, Tereza; Jindřichová, Barbora; Henke, Svatopluk; Yvin, Jean-Claude; Ferrieres, Vincent; Burketová, Lenka; Lipovová, Petra; Nguema-Ona, Eric (Frontiers in Plant Science, 2022)
Natural compounds isolated from macroalgae are promising, ecofriendly, and multifunctional bioinoculants which have been tested and used in agriculture. Ulvans for instance, one of the major polysaccharides present in Ulva spp. cell walls, have been tested for their plant growth-promoting properties as well as their ability to activate plant immune defense, on a large variety of crops. Recently, we have characterized for the first time an arabinogalactan protein-like (AGP-like) from Ulva lactuca, which exhibits several features associated to land plant AGPs. In land plant, AGPs were shown to play a role in several plant biological functions including cell morphogenesis, reproduction and plant-microbe interactions. Thus, isolated AGP-like proteins may be good candidates for either the plant growth-promoting properties or the activation of plant immune defense. Here, we have isolated an arabinogalactan protein-like (AGP-like) enriched fraction from Ulva lactuca and we have evaluated its ability to i) protect oilseed rape (B. napus) cotyledons against Leptosphaeria maculans, and ii) its ability to activate immune responses. Preventive application of the Ulva AGP-like enriched fraction on oilseed rape, followed by cotyledon inoculation with the fungal hemibiotroph L. maculans, resulted in a major reduction of infection propagation. The noticed reduction correlated with an accumulation of H2O2 in treated cotyledons and with the activation of SA and JA/ET signaling pathways in oilseed rape cotyledons. In parallel, an ulvan was also isolated from Ulva lactuca. Preventive application of ulvan also enhanced plant resistance against L. maculans. Surprisingly, reduction of infection severity was only observed at high concentration of ulvan. Here, no such significant changes in gene expression and H2O2 production were observed. Together, this study indicates that U. lactuca AGP-like glycoproteins exhibit promising elicitor activity and that plant eliciting properties of Ulva extract, might result not only from an ulvan-originated eliciting activities, but also AGP-like originated.